THE GLOOMY PICTURESQUE EMPOWERING LEADERSHIP THROUGH THE LENS OF WORK ENGAGEMENT - Pengcheng Zhang; Samaneh Gheibi (European Scientific Journal, ESJ, 2015)
The present research aims to first investigate a negative individual outcome that empowered staff experience and is theoretically relevant, however, not yet examined: work-family conflict. Furthermore, this study will examine if work engagement serves as mediator for the relationship between work-family conflict and empowering leadership.